Mobile communication systems to control UAVs: Measurements of QoS parameters - Silvério, A. (2021)
This paper proposes to identify a propagation model that considers the unmanned aerial vehicles (UAVs) unique characteristics, contemplating two actual wireless technologies, UMTS and LTE, which are theoretically capable of supporting a real-time video service admitting more than one quality index according to the RF conditions. Several measurements were made in a specific outdoor rural scenario in order to understand if the current network infrastructure is prepared to support this type of service using these vehicles, by simulating a real case scenario and considering critical locations where the loss of Quality of Service (QoS) can be significant due to the hole phenomenon that occurs over the antennas/base stations, raising the probability to occur handover.